Introducing U.S. Soccer Coach Education's Play-Practice-Play Coaching Model. (24th November 2020) - Currie, Stuart; Korgaokar, Ajit; Crawford, Zac; Pauwels, Barry
Abstract : The main objective of this article is to introduce soccer coaches and physical education teachers to the United States Soccer Federation's PPP model. A second objective is to provide coaches and teachers with a practical example that illustrates and explains each stage of the PPP model. The PPP model is broken down into three stages that include play 1 phase, practice, and play 2 phase.